PENINGKATAN PEMBELAJARAN LOMPAT TINGGI DENGAN MEDIA KARET DI SDN 12 BALAU MILUT - Timotius NG, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research is to improve learning the high jump with a rubber media as a tool in the fourth grade students of SDN 12 Balau Milut Kabupaten Sekadau . Forms of research is classroom action research. Research subjects in this study were all fourth grade students of SDN 12 Balau Milut Kabupaten Sekadau totaling 21 students. Learning the high jump with a medium rubber to provide convenience to students to always be active and brave movement high jump is easy and fun give suasanan new that has never been done before , the positive impact of such students do not experience fear , feel good and appropriate to their abilities owned by the students . In making the value of the start prasiklus , the first cycle and the second cycle increased systematically Keywords: High Jump, Media Rubber